Process Mining Success Factors and Their Interrelationships - Azumah Mamudu; Wasana Bandara; Moe T. Wynn; Sander J. J. Leemans (Business & Information Systems Engineering, 2024)
Process mining—a suite of techniques for extracting insights from event logs of Information Systems (IS)—is increasingly being used by a wide range of organisations to improve operational efficiency. Despite extensive studies of Critical Success Factors (CSFs) in related domains, CSF studies tailored to process mining are limited. Moreover, these studies merely identify factors and do not provide essential details such as a clear conceptual understanding of success factors and their interrelationships. Through a multi-phased approach (applying published process mining case studies, conducting two in-depth case studies and expert interviews), this paper presents an empirically validated process mining CSF model and CSF interrelationships. This validated CSF model identifies ten process mining CSFs, explains how these factors relate to the process mining context and analyses their interrelationships with regard to process mining success. The findings provide a guide for organisations to invest in the right mix of CSFs for value realisation in process mining practice.
Keywords: 000; Process mining; Success factors; Process mining success; Process mining impact; Factor interrelationships; Case studies; Expert interviews